ضرورة الفكر المقاصدي المعاصر في ترسيخ مبادئ الحضارة الإنسانية: دراسة تحليلية في ضوء التجربة الماليزية: The Necessity of Contemporary Purposive Thought in Consolidating the Principles of Human Civilization: An Analytical Study in Light of the Malaysian Experience - Abu Qar, Adibah; Al-Bogha, Mhmd Al-Hasan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
Contemporary purposive thought is characterized by deep understanding and analysis of matters in a logical way that corresponds to reality. It offers solutions that align with the priorities of human civilization. This research aims to elucidate contemporary purposive thought in its modern directions, highlighting its most important fields, namely: the domains of purposive thought in beliefs, ethics, legal politics, and financial transactions. It also examines the Malaysian experience in light of these fields, showcasing the endeavors of Malaysians, both people and government, in adopting the approach of purposive thought to comprehend and articulate reality, as well as to devise solutions for it. The Malaysian civilization was constructed, its people’s renaissance occurred, and its successful experience was showcased to the world. The research demonstrates the aspects through which the construction of society and human civilization is assessed, utilizing a deductive analytical approach. Contemporary purposive thought was deduced from contemporary scholars of maqasid (purposes) and analyzed in light of the Malaysian experience. The research concludes by suggesting solutions for nation-building through the unique Malaysian experience, which, if implemented in reality, would yield individual and societal development. This can be accomplished by adhering to the principles of contemporary purposive thought, which empowers humans as active participants and beneficiaries within the universe, as everything in this universe exists to serve humanity.